Clinical characteristics of unknown symptom onset stroke patients with and without diffusion-weighted imaging and fluid-attenuated inversion recovery mismatch. Issue 1 (January 2018) - Thomalla, Götz; Boutitie, Florent; Fiebach, Jochen B; Simonsen, Claus Z; Pedraza, Salvador; Lemmens, Robin; Nighoghossian, Norbert; Roy, Pascal; Muir, Keith W; Ebinger, Martin; Ford, Ian; Cheng, Bastian; et al.
Background: Diffusion-weighted imaging (DWI) and fluid-attenuated inversion recovery (FLAIR) mismatch was suggested to identify stroke patients with unknown time of symptom onset likely to be within the time window for thrombolysis. Aims: We aimed to study clinical characteristics associated with DWI-FLAIR mismatch in patients with unknown onset stroke. Methods: We analyzed baseline MRI and clinical data from patients with acute ischemic stroke proven by DWI from WAKE-UP, an investigator-initiated, randomized, placebo-controlled trial of MRI-based thrombolysis in stroke patients with unknown time of symptom onset. Clinical characteristics were compared between patients with and without DWI-FLAIR mismatch. Results: Of 699 patients included, 418 (59.8%) presented with DWI-FLAIR mismatch. A shorter delay between last seen well and symptom recognition (p = 0.0063), a shorter delay between symptom recognition and arrival at hospital (p = 0.0025), and history of atrial fibrillation (p = 0.19) were predictors of DWI-FLAIR mismatch in multivariate analysis. All other characteristics were comparable between groups. Conclusions: There are only minor differences in measured clinical characteristics between unknown symptom onset stroke patients with and without DWI-FLAIR mismatch. DWI-FLAIR mismatch as an indicator of stroke onset within 4.5 h shows no relevant association with commonly collected clinical characteristics of stroke patients. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01525290; URL:https://www.clinicaltrialsregister.eu . Unique identifier: 2011-005906-32.